Progression of BRAF-induced thyroid cancer is associated with epithelial-mesenchymal transition requiring concomitant MAP kinase and TGFβ signaling - Knauf, Jeffrey A (2011)
Mice with thyroid-specific expression of oncogenic BRAF (Tg-Braf) develop papillary thyroid cancers (PTC) that are locally invasive and have well-defined foci of poorly differentiated carcinoma (PDTC). To investigate the PTC-PDTC progression, we performed a microarray analysis using RNA from paired samples of PDTC and PTC collected from the same animals by laser capture microdissection. Analysis of 8 paired samples revealed a profound deregulation of genes involved in cell adhesion and intracellular junctions, with changes consistent with an epithelial-mesenchymal transition (EMT). This was confirmed by IHC, as vimentin expression was increased and E-cadherin lost in PDTC compared to adjacent PTC. Moreover, PDTC stained positively for phospho-Smad2, suggesting a role for TGFβ in mediating this process. Accordingly, TGFβ induced EMT in primary cultures of thyroid cells from Tg-Braf mice, whereas wild-type thyroid cells retained their epithelial features. TGFβ-induced Smad2 phosphorylation, transcriptional activity and induction of EMT required MAPK pathway activation in Tg-Braf thyrocytes. Hence, tumor initiation by oncogenic BRAF renders thyroid cells susceptible to TGFβ-induced EMT, through a MAPK-dependent process.